2018
DOI: 10.1002/14651858.cd011988.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal debridement versus no debridement for the postoperative care of patients undergoing endoscopic sinus surgery

Abstract: Sinonasal debridement versus no debridement for the postoperative care of patients undergoing endoscopic sinus surgery (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Understanding the normal peri-operative time toward healing can better guide clinical decisions as to the frequency and length of follow-up needed in the immediate post-operative period. Previous reports have shown that in the post-operative period, after sinus surgery, nasal debridement is associated with improved ostium patency and a lower rate of intranasal scarring [ 18 ]. As such, one hypothesis that could be deduced is that earlier mucosalisation of exposed bone may lead to less crusting, less need for debridement in the peri-operative period and possibly improved rates of longer-term patency.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the normal peri-operative time toward healing can better guide clinical decisions as to the frequency and length of follow-up needed in the immediate post-operative period. Previous reports have shown that in the post-operative period, after sinus surgery, nasal debridement is associated with improved ostium patency and a lower rate of intranasal scarring [ 18 ]. As such, one hypothesis that could be deduced is that earlier mucosalisation of exposed bone may lead to less crusting, less need for debridement in the peri-operative period and possibly improved rates of longer-term patency.…”
Section: Discussionmentioning
confidence: 99%
“…adhesion rates with or without debridement [26]. A metaanalysis on the benefit of sinonasal debridement after endoscopic sinus surgery stated low-quality evidence that postoper- ative debridement is associated with a significant lower adhesion rate after 3 months [27]. We therefore recommend postoperative sinonasal debridement in pituitary patients undergoing transsphenoidal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While debridement has been shown to reduce postoperative adhesions, assessment of multiple randomized controlled trials show no consistent benefit based on symptom scores [23]. Cochrane Database reviews on surgery for chronic rhinosinusitis and debridement have shown no benefit/ advantage compared to medical management (e.g., antibiotics, sinus irrigations, steroids) [24,25]. The subsequent advent of office balloon sinuplasty, which bypasses general anesthesia, has further accelerated intervention for this condition despite lack of clear benefit: since the introduction of CPT coding for this procedure in 2011, a sixfold increase in procedures (44 000 in 2017) and 433% increase in payments have been observed [26,27].…”
Section: Rationale For Surveillance For Benign Thyroid Nodulesmentioning
confidence: 99%